The Psychological and Demographic Factors of Quality of Life in Older Adults - Indra Yohanes Kiling; Johana Endang Prawitasari (Universitas Nusa Cendana, 2020)
This research aims to determine the relationship between psychological and demographic factors, which are dispositional optimism, and self-efficacy are the psychological factors, meanwhile home, sex and ethnicity as the demographic factors of quality of life in the older adults. The major hypothesis of this research proposed that there are positive relationship from both psychological factors and demographic factors to the quality of life in older adults. This study involved 53 older adult peoples. The result of multiple regression analysis shows that there is a positive relationship from all five variables to the quality of life in older adults as big as 76,5% (Adjusted R2= 0,765). This result means that both the psychological and demographic factors do have effective contributions to the quality of life in older adult people. The results of t-tests are also discussed.